Part One • An Introduction to Economics and the Economy
Having denoted Q* as the equilibrium quantity, then it must be that Q* = Qd = Qs. To solve for the equilibrium quantity Q* and the equilibrium price P* the demand and supply functions are used. With Q* the equilibrium quantity, for the buyers
Now, since P* is the same agreed-upon price by both buyer and seller, then a - bQ* = c + dQ*, giving the equilibrium quantity, Q*, as
Q* = (a - c)/(b + d). To find P* substitute (a - c)/(b + d) in the supply (or demand) function. P* = c + d(a - c)/(b + d), thus P* = (ad + bc)/(a + d).
The equilibrium is (Q*, P*) = [(a - c)/(b + d), (ad + cb)/(a + d)].
The market equilibrium may also be represented diagrammatically, as shown in Figure A -1.
Was this article helpful?